Differential diagnosis of pancreatic cancer and chronic pseudotumor pancreatitis: literature review - A. A. Perminova; M. D. Khanevich; G. M. Manikhas; N. Yu. Kokhanenko (Вестник хирургии имени И.И. Грекова)
Every year more and more pancreatic lesions are accidentally detected. Besides genetic predisposition and environmental factors, chronic pancreatitis is by far the greatest risk factor for pancreatic malignancy. Currently, there are no screening methods for early detection of pancreatic cancer and its differential diagnosis with chronic pancreatitis. Precise characterization of pancreatic lesions is crucial in deciding whether to use active surgical tactics or dynamic observation, which surgery to perform.